2021
DOI: 10.3389/fpsyt.2021.655130
|View full text |Cite
|
Sign up to set email alerts
|

Coping With the Experiences of Intimate Partner Violence Among South African Women: Systematic Review and Meta-Synthesis

Abstract: Background: Intimate partner violence (IPV) continues to be a serious problem worldwide. South Africa has a high prevalence of women experiencing IPV. Although much research reports on the prevalence rates, risk factors, and consequences of IPV, fewer studies report on how women deal with the experiences of IPV.Objective: This systematic review of the empirical literature aimed to identify and synthesize the best available evidence on women's experiences of coping with IPV in South Africa.Methods: A four-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…The intervention development was carried out globally in consultation with researchers and practitioners in five LMICs (South Africa, Jamaica, Malaysia, the Philippines, and Sri Lanka) to account for variations in contexts in preparation for scaling up the intervention in the future. These countries were purposefully selected because of pre-existing partnerships with research institutions and organisations in the locations, and because of the high rates of IPV reported in these countries [ 43 47 ].The formative evaluation was carried out in Kingston, Jamaica in order to assess engagement with the chatbot and the intervention content. Jamaica was selected as the location for the formative evaluation due to the high levels of IPV reported in the country and because existing collaborations with research partners and community organisations in the country made rollout more feasible.…”
Section: Methodsmentioning
confidence: 99%
“…The intervention development was carried out globally in consultation with researchers and practitioners in five LMICs (South Africa, Jamaica, Malaysia, the Philippines, and Sri Lanka) to account for variations in contexts in preparation for scaling up the intervention in the future. These countries were purposefully selected because of pre-existing partnerships with research institutions and organisations in the locations, and because of the high rates of IPV reported in these countries [ 43 47 ].The formative evaluation was carried out in Kingston, Jamaica in order to assess engagement with the chatbot and the intervention content. Jamaica was selected as the location for the formative evaluation due to the high levels of IPV reported in the country and because existing collaborations with research partners and community organisations in the country made rollout more feasible.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the reliance of social support to cope was found in the groups who did not experience IPV. Research focusing on coping strategies among women dealing with IPV revealed that victims found their families, friends, and neighbours to be supportive and reliable resources for assistance [ 25 ]. Our study, however, did not find that participants experiencing IPV relied on family and social support structures as a way of coping, in such situations.…”
Section: Coping Strategiesmentioning
confidence: 99%
“…In the IPV context, coping strategies are more diverse, according to a systematic review of US studies, it was found that religious or spiritual reliance and active abuse resistance were common whilst self-criticism and substance misuse were less common [ 24 ]. Contrary to this, a systematic review of South African studies found that many of the women who had experienced IPV used avoidance and distraction as a way to cope and this included substance abuse/misuse [ 25 ]. Seeking help has also been found to be a coping strategy among some IPV survivors, however this varies and is dependent on the severity of the victimization as well as resources available to the woman [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Domestic abuse affects 1.6 million women and 757,000 men in the United Kingdom in 2019 (ONS, 2020), while 43.3 percent of women in developing countries reported physical abuse, according to a study in India (ICRW, 2000, p.9). Intimate partner violence (IPV) is prevalent in South Africa, with 20% to 50% of women experiencing violence at some point in their lives (Sere et al, 2001). In Ghana, the prevalence of intimate partner violence is high, with 43 percent of women with partners or spouses reporting experiencing at least one type of IPV in the previous year (ISSER et al, 2019, p.18).…”
Section: The Prevalence Of Gender-based Violence Worldwidementioning
confidence: 99%